Valuable, rare, inimitable resources and organization (VRIO) resources or valuable, rare, inimitable resources (VRI) capabilities: what leads to competitive advantage? - Cardeal, N. (2012)
The resource-based view (RBV) argues that valuable, rare, inimitable resources and organization (VRIO) lead to competitive advantage. Dynamic capabilities (DC) are a comparatively new field and the related literature is mainly conceptual. Capabilities can be considered as the firm’s routines and processes. We argue that the “O” in VRIO refers to DC. DCs are the “organization” needed to transform bundles of resources into competitive advantage. Consequently, does competitive advantage stem from VRIO resources or from VRI capabilities? Through a case study we analyzed the development of one capability in a medium-sized Portuguese footwear manufacturer. After reviewing the process of development of the capability, we performed a VRIO test for each of the resources it exploits and a VRI test of the capability. We can conclude that none of the resources contributing to the capability are VRIO, but the capability is VRI.